PARADIGMA PENDIDIK TERHADAP PENERAPAN KURIKULUM MERDEKA BELAJAR DI RAUDHATUL ATHFAL SWASTA HARAPAN BANDAR PULO - Sembiring Depari , Rizky; Dahlan, Zaini; Ade Yusuf, Rizky; Hidayat, Taufik (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
The implementation of the independent curriculum involves teachers, because teachers are the main actors in implementing the curriculum. This article aims to explain teachers' perceptions of the implementation of the independent curriculum at Raudhatul Athfal Swasta Harapan Bandar Pulo. This research uses a qualitative descriptive method. Research data collection techniques by conducting unstructured interviews. The respondents are class teachers. The research results show that: (1) Teachers support the Independent Learning Curriculum; (2) Training and socialization regarding the Independent Learning Curriculum has not been carried out optimally; (3) The changes experienced by teachers lie in students becoming active and increasing the sense of mutual cooperation due to project-based learning; (4) The teacher's obstacle in implementing the Independent Learning Curriculum lies in the administration system.